Innovation and Key Benefits of Business Models in Blockchain Companies - Aini, Qurotul; Manongga, Danny; Rahardja, Untung; Sembiring, Irwan; Efendy, Rifan (Blockchain Frontier Technology, 2023)
Existing business models are changed and disrupted by blockchain technology, which warrants more research. This study tries to describe the phenomena of blockchain technology in relation to business model innovation in the enterprise ecosystem on the basis of that. Blockchain technology has been shown to increase organizational performance empirically. The value system concept is used in this study to explain this phenomena. This study employs a multiple-case study to respond to research questions using abductive reasoning. Overall, the outcomes According to this study, blockchain technology benefits an organization in four different ways: I value capture through higher profitability; (ii) value creation through private partnerships; (iii) value delivery through smart contracts; and (iv) value proposition that drives value by raising the organization's business value through operational improvements. This report also suggests a blockchain ecosystem with various private and consortium organizations. Private ecosystem focused on internal organizational performance enhancement within one corporate enterprise. The consortium ecosystem, on the other hand, is focused on fostering corporate cooperation.